Postharvest losses of fresh tomato production in Cameron Highlands and Lojing Highlands, Malaysia - Lee, Kwee Tiong (2020)
In Malaysia, postharvest losses of vegetables are estimated to be about 20-50%. Tomato is the most important high-value vegetable crops with enormous potential for export in Malaysia. But quantitative evidence of postharvest losses of tomato is limited due to less attention has been given to the study on postharvest losses. To the best knowledge of the author, there is no research study on postharvest losses of tomato in Cameron Highlands and Lojing Highlands using the approach of estimating the losses at the identified critical loss points of each of the key players along the agrifood supply chain. The goal of this study was to extend the effort made by previous authors by estimating the postharvest losses of fresh tomato production using a different approach, sampling method instead of tracking or direct measurement. As the problem of high postharvest losses that usually occur on the farm in developing countries and farmers’ income was affected the most. It is, therefore, necessary to conduct a study on determining factors influencing postharvest losses of tomato at the farm level. As the adoption of postharvest practices is found to be negatively correlated to postharvest losses, it is, therefore, necessary to conduct a study on determining determinants influencing farmers' adoption on postharvest practices. Thus, the main objective of this study is to estimate the postharvest losses of fresh tomato production in Cameron Highlands and Lojing Highlands. A combination of multistage random sampling technique and snowball sampling techniques were used to select tomato farmers and key players at various stages of the tomato supply chain. Data were collected through personal interviews using a structured questionnaire from 133 respondents which included 110 farmers, 11 collectors, 4 wholesalers, and 8 retailers. Descriptive analysis was used to summarize the socio-economic and demographic profiles of the respondents and the estimation of postharvest losses of tomato. Factor analysis nd multiple linear regression analysis were used to determine the factors influencing the postharvest losses of tomato at the primary production level. Chisquare analysis was used to determine the association between farmers’ adoption of postharvest practices and socio-economic and demographic profiles. Logistic regression analysis was used to determine determinants affecting farmers' decisions on the adoption of postharvest practices. The findings revealed that estimated postharvest losses at the farm, collector, wholesale markets, and retail levels were 5.43%, 2.79%, 0%, and 11.51 %, respectively. The results of multiple regression analysis suggested that skilled harvesters and the adoption of postharvest practices were the two factors found to have an inverse relationship with postharvest losses of fresh tomato at the farm level. On the other hand, harvesting methods, storage, and poor processing and packaging were the three factors found to be positively related to postharvest losses of fresh tomato at the farm level and these results confirmed the hypotheses of this study. The results of Chi-square analysis revealed that farmers’ age, experience, and awareness level were significantly associated with farmers’ adoption of postharvest practices. Concerning determinants that influence farmers’ decision on the adoption of postharvest practices, the results from logistic regression analysis indicated that farming experience, awarenessknowledge of postharvest practices, and perceptions of postharvest practices were found statistically significant with farmers’ decision on adoption of postharvest practices. The policymakers should find ways to improve farmers’ knowledge on postharvest practices as well as to improve their perceptions about the benefits of postharvest practices towards reducing postharvest losses. Hence, more farmers will adopt the postharvest practices as recommended by the policymakers. This study adds to the body of knowledge of postharvest losses along the food supply chain literature by increasing understanding of postharvest losses problems, particularly the tomato supply chain in Malaysia. Effective measures and interventions can be developed based on the identified factors and causes influencing postharvest losses. Thus, the reduction of postharvest losses can be achieved, and the business performance of farmers can be improved.